POTENTIAL OF SUPERIOR VARIETY KEMIRI SUNAN AS RESOURCES FOR BIODIESEL MATERIAL - . SYAFARUDDIN; AGUS WAHYUDI (Puslitbang Perkebunan, 2012)
Biodiesel needs to be developed seriously as an alternative energy due to decrease in fossil fuel resource. Biodiesel had been planned by OPEC to be one of energy supply resource. Kemiri sunan (Reutealis trisperma (Blanco) Airy Shaw) is one of potential crops for the biodiesel purpose. Besides containing high oil, it also has specific characteristics such as fast growing and vigority, wide range of elevation (from low to high lands), high productivity, and good for conservation crop. The first step had been done to save the potential genetic material of kemiri sunan by variety registry to Center for Plant Variety Protection dated 25 May 2009. Based on observation in two populations (Majalengka and Garut), rendemen of kernel oil of Jumat population (Kemiri Sunan 2 Variety), about 47.21-56.00% was better than Cinunuk and Banyuresmi populations (Kemiri Sunan 1 Variety), about 40.00-43.11% and 38.10-42.00%, respectively. In general, Kemiri Sunan 2 variety was good in performance, characteristics, and quality. Results of DNA analyses using Random Amplified Polymorphic DNA and 16 primers in Majalengka and Garut regions showed narrow variations of kemiri sunan accession. It was indicated by one group containing seven samples (Cinunuk, Cidadap, Cicalung, Waru, Kemiri Sunan 2 Variety, Babakan, and Widara) with the similarity level of 100%, while Bodas one with >90%. Other results showed that Kemiri Sunan 1 variety had wide variation and was separated far away from the other 8 samples with the similarity level of 65%. This phenomenon was interesting to be studied according to the possibility of this individual to have better genetic characteristic possibly useful as genetic material for breeding program. Conventional breeding will be success if hybridization among individual having wide genetic variation to obtain progeny with the wide variation as well. The new released variety of kemiri sunan can be used as a new alternative of biodiesel resource. In addition, it is possible to gain added values by the utilization of existing germplasm resources.Key words: Reutealis trisperma (Blanco), high yielding varieties, alternative energy sources.